Predicting Factors of Plasma HIV RNA Undetectability after Switching to Co-Formulated Bictegravir, Emtricitabine, and Tenofovir Alafenamide in Experienced HIV-1 Patients: A Multicenter Study - Monica Basso; Giuliana Battagin; Stefano Nicolè; Maria Cristina Rossi; Francesco Colombo; Nicole Pirola; Stefano Baratti; Silvia Storato; Federico Giovagnorio; Vincenzo Malagnino; Grazia Alessio; Antonio Vinci; et al. (Viruses, 2023)
Switching to bictegravir, emtricitabine, and tenofovir alafenamide (BIC/FTC/TAF) from other antiretroviral regimens is safe and effective for virologically suppressed people living with HIV (PLWH). The term virological suppression includes both low but detectable HIV viremia and undetectable HIV viremia, and the latter is possibly associated with a lower immune activation state. Herein, we describe a 24-month follow-up of experienced PLWH with plasma HIV RNA undetectable or detectable < 50 copies/ml switching to BIC/FTC/TAF. A previous 12-month monitoring was available, and the factors correlated with treatment efficacy. This retrospective multicenter study included PLWH who switched to BIC/FTC/TAF in the period of 2019–2022, and who were HBsAg and HCV RNA negative. The follow-up study times were 6 (T6), 12 (T12), 18 (T18), and 24 (T24) months after the switch (T0). Survival analysis with multiple-failure-per-subject design, Kaplan–Meier survival estimates, multivariate analysis of variance, multilevel linear regression, and a hierarchical ordered logistic model were applied. A total of 329 PLWH had plasma HIV RNA which was either undetectable or detectable at <50 copies/mL at T0, and 197 responded to all inclusion criteria: M/F 140/57; the median CD4+ cell count was 677 cells/mm3; and HIV RNA at T0 was undetectable in 108 patients. Most of the 197 patients (122, 61.9%) were on a previous INSTI-based regimen. HIV RNA undetectability was more frequent at each follow-up point in patients with HIV RNA that was undetectable at T0, and it showed a higher frequency throughout the follow-up period in patients with always-undetectable HIV RNA in the 12 months before the switch. A higher nadir CD4 cell count had a predictive role, and HBcAb positivity had no influence. In conclusion, the switch could be programmed and possibly delayed on a case-by-case basis in order to achieve persistent plasma HIV RNA undetectability. Undiagnosed loss of HBcAb has no detrimental consequences on the response to BIC/FTC/TAF.